Wide Tuning Range Wavelength-Swept Laser With Two Semiconductor Optical Amplifiers - Oh, W. Y. (2005)
We demonstrate a wide tuning range high-speed wavelength-swept semiconductor laser based on a polygon scanning filter that is common to two laser cavities. Linear wavelength tuning was achieved over 145 nm around 1310 nm at a tuning repetition rate of 20 kHz. The wavelength tuning filter is expandable to accommodate multiple semiconductor optical amplifiers for further widening of the laser wavelength tuning range.